2019
DOI: 10.1111/jog.13911
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of 5p deletion syndrome: Report of five cases

Abstract: It is difficult to prenatally identify 5p deletion (−) syndrome. Here, we report five cases of 5p‐ syndrome diagnosed by invasive prenatal diagnosis. Of them, three had a small cerebellum in the second trimester. In one case, a prominent renal pelvis and an absent nasal bone were also found in the first trimester. However, there were no abnormal ultrasound findings in the other two cases. Two cases had noninvasive prenatal testing and one showed a ‘5p‐ syndrome positive result’ because of reduced amount of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
(21 reference statements)
0
16
1
Order By: Relevance
“…The incidence of CdCS in our cohort was around 0.034% (12/35,233), much higher than the previously reported incidence of 1/50,000–1/15,000 in live births [25]. According to our retrospective analysis, 6/12(50%) of our cases had an isolated 5p terminal deletion, the proportion (54.5%) was lower than that (62.5%) reported by Han et al in eight prenatal cases [20] and greater than that (20%) reported by L. Mark et al [22]. 6/12(50%) of cases characterized by unbalanced translocation, the sex ratio of our CdCS cases was 7/5 (female/male), consistent with the rate of postnatal series by Nguyen, J. M.et al [2].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The incidence of CdCS in our cohort was around 0.034% (12/35,233), much higher than the previously reported incidence of 1/50,000–1/15,000 in live births [25]. According to our retrospective analysis, 6/12(50%) of our cases had an isolated 5p terminal deletion, the proportion (54.5%) was lower than that (62.5%) reported by Han et al in eight prenatal cases [20] and greater than that (20%) reported by L. Mark et al [22]. 6/12(50%) of cases characterized by unbalanced translocation, the sex ratio of our CdCS cases was 7/5 (female/male), consistent with the rate of postnatal series by Nguyen, J. M.et al [2].…”
Section: Discussioncontrasting
confidence: 52%
“…These critical region sizes were too small and beyond the G-band’s resolution. Furthermore, some of 5p- syndrome cases might also be missed by conventional cytogenetic analysis alone [22]. Thus, combined CMA with karyotyping could be a definitive method for diagnosis of 5p- syndrome, and it can be expected that more cases of CdCS would be detected since routine clinical use of CMA in prenatal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to triploid and numerical chromosome abnormalities, pathogenic chromosome microdeletion/duplication also leads to poor fetal prognosis. For example, Wolf-Hirschhorn syndrome mostly results in developmental retardation, unusual faces and structural abnormalities, and Miller-Dieker syndrome can be complicated by pachygyria; 22q11.21 microdeletion syndrome often has various degrees of cardiac malformations [ 1 – 6 ]. If pathogenic chromosome microdeletion/duplication can be diagnosed prenatally, the births of children with such severe congenital defects can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…While the prenatal detection of cleft lip is high, the detection rate of subtle abnormalities of face such as low-set or posteriorly rotating ear, triangular face, down-slanting palpebral fissures, or a long and marked philtrum remains low [ 14 , 15 ]. These subtle abnormalities may be features of rare but severe genetic disorders such as 5p deletion syndrome or RASopathy, which require chromosome microarray analysis or targeted sequencing for RASopathy genes.…”
Section: High-resolution Ultrasonographymentioning
confidence: 99%